Formation of Qur'ani Character in Children at TPQ Miftahul Ulum Cidokom Gunung Sindur Bogor - Siti Padilatul Musyaropah; Matnur Ritonga (Yayasan Adra Karima Hubbi, 2024)
Background. Education is defined as a learning process throughout human history. National education functions to develop a sense of loyalty and strength as citizens among the nation's people and improve their ability to maintain their way of life. Miftahul Ulum Al-Quran Education Park (TPQ) is an non-formal organization that prioritizes Al-Quran education in the context of character development initiatives in the Cidokom Village environment, Gunung Sindur District, Bogor. Purpose. The aim of this research is to understand the implementation of the TPQ Miftahul Ulum education program in relation to the child-teacher ratio in the Cidokom Village community, as well as the obstacles faced during program implementation and strategies for overcoming them. Method. This research used a qualitative descriptive approach at TPQ Miftahul Ulum, with Purposive Sampling and Snowball Sampling techniques to select informants. Data was collected through observation, interviews and documentation. Data analysis follows the Miles and Huberman model, with validity using triangulation of sources and techniques. Results. The results of this research show that the implementation of the educational program is an effort to realize children's character education at TPQ Miftahul Ulum. Conclusion. Al-Quran education has an important role in developing moral character through peer pressure, teaching perseverance and love in developing religious, personal, and communicative qualities in children at an early age.